(untitled) (Ciudades, 2018)
In metropolis, population and activities are being transformed in a level never seen before. The logic of the residential behaviours get transformed and tend to reconciliate (or to oppose) to the cosmopolitan logic ones. Taking as a starting point, the geographical and socio-urbanistics dynamics of the city of Lisbon and observing the genesis and transformation of a paradigmatic quarter of the outskirts of the Portuguese capital (Reboleira, Amadora), this article tries to reflect in a short way, the process of urban reclassification and its interaction with the metropolitan processes.